(untitled) (Research, Society and Development, 2022)
Objective: to report the experience of nursing students in carrying out a social action focused on the mental health of adolescents. Method: this is a descriptive, qualitative research, developed from the experience of nursing students in a health action developed with 60 adolescents from a public school of reference in the city of Timon, Maranhão. Results and discussions: It became evident that mental health is the foundation of the entire human evolutionary process. In this sense, during the action, we noticed the existence of a warped scenario of afflicted adolescents about this transition phase from high school to possibly higher education, associated with social pressure for approval, as well as the persistent doubt of professional choice. Moreover, such anxieties, in turn, are able to go beyond the school environment, reaching their interpersonal relationships, being notable catalysts for the growing incidence of psychological disorders. Conclusion: in this context, it was understood that the family and the school, as social institutions, are undoubtedly configured as means to identify, teach and discuss this issue, as well as provide support for this public, since, at the epidemiological level, they are characterized as the main victims of anxious and depressive disorders. In this lens, the remarkable role of alternative and complementary therapies in the process of self-care and self-knowledge by adolescents stands out as a supplementary measure in this scenario of undeniable concern.